Fine-scale habitat selection limits trade-offs between foraging and temperature in a grassland bird. (29th March 2021) - Londe, David W; Elmore, R Dwayne; Davis, Craig A; Fuhlendorf, Samuel D; Hovick, Torre J; Luttbeg, Barney; Rutledge, Jimmy
Abstract: Many species are frequently faced with the decision about how to balance the use of thermal refuge against access to food resources. We evaluated the habitat use of female greater prairie chickens ( Tympanuchus cupido ) to assess the potential for trade-offs between thermal conditions and food resources during the habitat selection process. Our objectives were to 1) compare near-ground temperatures, invertebrate availability, and vegetation characteristics at sites used by greater prairie chickens to conditions at random landscape locations in various time since fire patches and 2) assess changes in conditions at used sites throughout the day to determine if selection for resources changes relative to ambient conditions, resulting in trade-offs between foraging sites and thermal refuge. We found that greater prairie chickens primarily used patches 0–12 months postfire that had relatively high abundances and biomasses of invertebrates compared to other time since fire patches. Greater prairie chickens further modified their selection at relatively fine spatial scales within these food-rich patches to select for areas with cooler temperatures during the hottest part of the day. The use of thermal refuge did not appear to influence the access to food resources as invertebrate abundance and biomass at used sites were consistent throughout the day. Our results show that food resources and thermal cover influences habitat selection for greater prairie chickens, but there was little evidence for trade-offs during the habitat selection process. Consideration of spatial and temporal scales is critical for evaluating trade-offs in habitat selection for animals and this research provides insights into the decision-making process by prairie chickens. Abstract : Greater prairie chickens balance the thermal environment and foraging by modifying their behaviors at fine spatial and temporal scales. Animals are frequently faced with trade-offs between thermal conditions and food resources. Our results show that, in a grassland managed for vegetation heterogeneity, prairie chickens avoid trade-offs by selecting sites with cooler microsite temperatures in food-rich patches during the hottest parts of the day.